A biophysical and structural analysis of the interaction of BLNK with 14-3-3 proteins - Soini, Lorenzo; Leysen, Seppe; Davis, Jeremy; Ottmann, Christian (Journal of structural biology, 2020)
[Display omitted] •Phosphorylation of BLNK at Thr152 is important for 14-3-3 binding.•A 14-3-3σ/BLNKpT152 crystal structure confirms the binding mechanism.•BLNKpT152 binds to 14-3-3 proteins with micromolar affinity.•BLNK Ser285 has been confirmed to be an additional 14-3-3 binding site.•pThr152 and pSer285 could regulate the binding to 14-3-3 according to the gatekeeper model. B-cell linker protein (BLNK) is an adaptor protein that orchestrates signalling downstream of B-cell receptors. It has been reported to undergo proteasomal degradation upon binding to 14-3-3 proteins. Here, we report the first biophysical and structural study of this protein-protein interaction (PPI). Specifically, we investigated the binding of mono- and di- phosphorylated BLNK peptides to 14-3-3 using fluorescent polarization (FP) and isothermal titration calorimetry assays (ITC). Our results suggest that BLNK interacts with 14-3-3 according to the gatekeeper model, where HPK1 mediated phosphorylation of Thr152 (pT152) allows BLNK anchoring to 14-3-3, and an additional phosphorylation of Ser285 (pS285) by AKT, then further improves the affinity. Finally, we have also solved a crystal structure of the BLNKpT152 peptide bound to 14-3-3σ. These findings could serve as important tool for compound discovery programs aiming to modulate this interaction with 14-3-3.